Equipment contact surfaces as sources of Staphylococcus carrying enterotoxin-encoding genes in goat milk dairy plants. (December 2020) - De Leon, Candice M.C.G.; Sousa, Francisca G.C.; Saraiva, Mauro M.S.; Givisiez, Patricia E.N.; Silva, Núbia M.V.; Vieira, Rafael F.C.; Oliveira, Celso J.B.
Abstract: Potential contamination sources and the enterotoxigenic profiling of Staphylococcus isolates were investigated in four goat dairy plants. Samples (n = 160) were collected from different processing points in five samplings. Staphylococcus spp. isolates were confirmed by polymerase chain reaction and genotyped using repetitive extragenic palindromic PCR (Rep-PCR). Classical ( sea, seb, sec, sed ) and novel ( seg, seh, sei ) staphylococcal enterotoxin-encoding genes were detected by PCR. seb, sec, see and sei were identified in isolates originated from raw and pasteurised milk, pre- and post-pasteurisation tanks and wall surfaces. SE-harbouring isolates were mostly identified as non-aureus staphylococci. Genotypic profiles and contamination levels indicate that the packaging machine is a critical point for staphylococcal contamination. Equipment surfaces are important contamination sources to pasteurised milk considering the indistinguishable genotypic patterns of isolates from pre- and post-pasteurisation points. Cleaning and disinfection of milk contact surfaces should be revisited to warrant quality and safety of goat milk.